Poly (itaconic acid) functionalized lignin/polyvinyl acetate composite resin with improved sustainability and wood adhesion strength - Ghosh T.; Elo T.; Parihar V.S.; Maiti P.; Layek R. (My University, 2025)
In this current scenario, there is a broad range of use of resins in both domestic and industrial applications. Especially the importance of resins for adhesive in the wood industry is inevitable. But most of the commercially available resins for adhesive application are prepared of formaldehyde or fossil fuel-based resources which possess serious health issues. Henceforth, development of environmentally friendly resin from renewable resources through a cost-effective technique is a challenging task. Motivated by these facts and prospects, we present a novel technique for addressing non-renewability difficulties while also improving adhesive strength of the material. In this study, lignin-based composite resin with enhanced sustainability and adhesion strength have been achieved by a simply mixing of high concentration of poly (itaconic acid)-functionalized-lignin (P(IA)-f-Lignin) and aqueous emulsion of polyvinyl acetate. The P(IA)-f-Lignin was synthesized by in-situ free radical polymerization of partly neutralized IA in the presence of aqueous lignin dispersion at 90 °C using ammonium persulfate as initiator. The formation of P(IA)-f-Lignin was confirmed by Fourier transform infrared spectroscopy (FTIR), X-ray photoelectron spectroscopy (XPS), nuclear magnetic resonance (NMR), field emission scanning electron microscope (FESEM) and thermogravimetric analysis (TGA). Here, we have been fabricated 20, 30, 40, 50, and 60 wt% of P(IA)-f-Lignin containing composite resin with desired amount of aqueous emulsion of polyvinyl acetate (PVAc). The changes in physico-chemical interactions were established by FTIR analysis. Various properties like viscosity, thermo-stability, and adhesive properties of all the formulated composite resin were inspected thoroughly. The composite containing 40 wt% of P(IA)-f-Lignin shows excellent improvement of adhesion strength from 3.32 ± 0.12 MPa to 7.83 ± 0.45 MPa. These fabricated composite resin with a high concentration of bio-based P(IA)-f-Lignin content and strong adhesion strength is very promising for fabrication of biobased adhesives with improved sustainability. © 2022 The Authors